A CRITICAL ANALYSIS OF ADAM SMITH IN BEIJING - Kawakami Gonçalves Costa, Simone (Revista Cronos, 2024)
Giovanni Arrighi, Italian economist and historian, was undoubtedly one of the most important exponents of the theoretical current known as world-system. His last work, entitled Adam Smith in Beijing Origins and Foundations of the 21st Century, in 2007, a year before his death, was published at a time when the international situation was and that is to say, continues to be marked by new tensions. Even though Giovanni Arrighi did not live to see the consequences of the 2008 economic crisis, the resurgence of tensions between China and the United States, or even the emergence of a new international right, the questions raised in his latest work are useful for thinking in which direction the international system can be reordered. In this article, the thesis of Chinese peaceful rise as a potential new hegemon and likely promoter of a new, multipolar, and less bellicose order is critically analyzed based on considerations posed by the strands derived from the theory of imperialism, in addition to an assessment of the class constitution of the Modern China.